CRUDE OIL MANAGEMENT INTO DIESEL FUEL IN WONOCOLO VILLAGE: LOCAL WISDOM, ENVIRONMENTAL RISKS, AND LEGAL FRAMEWORK GAPS - Rizal, Tulus Afriyan; Madjid, Adnan; Uksan, Arifuddin (Yayasan Amanah Nur Aman, 2025)
The management of crude oil into diesel in Wonocolo Village, Bojonegoro, is a traditional practice inherited from the Dutch colonial era, combining local wisdom with the community’s historical values. The background of this study arises from the need to understand how traditional oil processing practices impact the environment and how legal gaps affect the sustainability of these activities. This study aims to analyze diesel management in Wonocolo Village from the perspectives of local wisdom, environmental risks, and compliance with regulations, particularly Permen ESDM 2025. The method used is a qualitative approach, with data collected through in-depth interviews with seven respondents, field observations of processing facilities, and document studies related to regulations and alternative fuels such as biofuel and green diesel. The results indicate that traditional practices remain effective in producing diesel with high community involvement, but pose significant environmental risks due to liquid and solid waste being discharged directly into soil and waterways. In addition, limited regulatory knowledge creates a legal grey area. This study emphasizes the need to integrate local wisdom, technological modernization, environmental education, and adaptive regulations to establish sustainable, safe, and legally compliant diesel management practices.